Optimization of protease production by a strain of Bacillus species isolated from dairy industrial effluent - Mrs. Snehal A. Masurkar, Dr. S. C. Kale, Miss. Prajakta Jagtap, Shilpa.S.Ruikar (International Journal of Advanced Science and Technology, 2020)
Proteases are important enzymes used in variety of industries like food, dairy, detergent, pharmaceutical, and leather industries. The present studies were aimed at isolating highly proteolytic Bacillus species strains were isolated and optimization of protease production using the best protease producer. The Bacillus species were isolated from dairy industry effluent samples by using enrichment culture technique followed by isolation on solid media (nutrient agar). The isolated Bacillus spp. were screened for their proteolytic activities using milk agar .The best protease producing strain obtained was designated as DsB1 and was subjected to optimization studies with respect to PH ,incubation period, carbon temperature and nitrogen sources, employing submerged fermentation technique ,and using mineral salt medium. Studies on optimization showed that optimum temperature was 250c, optimum PH was 7.00 and optimum incubation period was 120 hrs. Amongst the carbon sources tested glucose was the best and amongst the nitrogen sources tested best nitrogen source was yeast extract.